Registro del enrollador de las hojas, Amorbia cuneana (Walsingham) (Lepidoptera: Tortricidae), en zarzamora en Rancho Huatarillo, Peribán, Michoacán - Juárez-Gutiérrez, Ana Celestina; Martínez, Ana Mabel; Figueroa, José Isaac; Rebollar-Alviter, Ángel; Aguilera-Peña, María Martha; Pineda, Samuel (Instituto de Ecología, A.C., 2015)
The leafroller, Amorbia cuneana (Walsingham) (Lepidoptera: Tortricidae), is recorded for the first time in blackberry (Rubus sp. cultivar Tupi) in Rancho Huatarillo, Municipality of Peribán, in the state of Michoacán, Mexico. It is important to assess the damage that this insect may cause to the plants, in order to avoid the possibility that it reach the pest status in the later crop.